1987
DOI: 10.3758/bf03334730
|View full text |Cite
|
Sign up to set email alerts
|

Attentional control of visual suffix effects

Abstract: An experiment was performed to compare the effects of an attentional manipulation and four suffix conditions on the recall of auditorily presented numerical sequences. In the nonattention condition, in which a suffix was described as a recall cue, spoken suffixes produced large end-ofsequence performance decrements; lipread suffixes produced similar, although smaller, effects. Suffixes "drawn" through the air on a card background (drawn) and those printed on a card (graphic) led to no significant end-of-sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Similarly, Nairne and Crowder (1982, Experiment 2) found that a silently mouthed suffix did not impair recall of a vocalized list as much as did a vocalized suffix. Manning (1987) found similar results with an auditorily presented list, provided that subjects did not have to attend to the suffix. In order to interfere maximally, the suffix must actually be heard.…”
Section: Modality Effects In Stm 413supporting
confidence: 63%
See 2 more Smart Citations
“…Similarly, Nairne and Crowder (1982, Experiment 2) found that a silently mouthed suffix did not impair recall of a vocalized list as much as did a vocalized suffix. Manning (1987) found similar results with an auditorily presented list, provided that subjects did not have to attend to the suffix. In order to interfere maximally, the suffix must actually be heard.…”
Section: Modality Effects In Stm 413supporting
confidence: 63%
“…However, in these experiments, the direct comparison between the effects of lip-read and heard suffixes on recall of auditorily presented lists was not made.. Manning (1987) did compare several different types of suffixes on recall of auditory lists, and her results indicate that the effects of lip-read and auditory suffixes are not the same. When subjects could ignore the suffix, the lip-read suffix did not produce nearly as much interference as a heard suffix did; only when the subjects had to articulate the lip-read suffix before recalling the memory items were the effects of the lip-read suffix similar in magnitude to those of a heard suffix.…”
Section: Studies On Lip-read Stimulimentioning
confidence: 90%
See 1 more Smart Citation
“…A final item that is not to be recalled (a suffix item) but is acoustically similar to the list items impedes performance in the latter part of the list. Greenberg & Engle (1983) found that such a suffix impeded performance of the last one or two items whether or not the suffix had to be attended, although attention modulated the suffix effect earlier in the list (see also Manning, 1987;Routh & Davidson, 1978). For recall of visual stimuli, irrelevant-speech effects (Salamé & Baddeley, 1982) demonstrate the passive, automatic nature of sensory storage.…”
mentioning
confidence: 99%
“…One exception that is most difficult to interpret involves the large body of data showing the presence of recency and suffix effects for lipread (e.g., see Campbell & Dodd, 1980) and mouthed stimuli (e.g., see Campbell, Garwood, & Rosen, 1988;Greene & Crowder, 1984), which are not auditory. Additionally, lipread suffixes, which are visual, produce decrements in recency on auditory sequences (e.g., see Manning, 1987;Spoehr & Corin, 1978).…”
mentioning
confidence: 99%